2017
DOI: 10.1016/j.riem.2017.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Diseño de un ECOE para evaluar habilidades clínicas en neurología en estudiantes del quinto año

Abstract: Diseño de un ECOE para evaluar habilidades clínicas en neurología 249 Conclusiones: El ECOE permite evaluar las habilidades clínicas de forma planificada. Los elementos fundamentales para su diseño son: el comité de examen, tabla de especificaciones, diseño de estaciones y logística del examen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 21 publications
(44 reference statements)
0
2
0
4
Order By: Relevance
“…The OSCE, as a valid and reliable instrument according to the results from this study and as stated by diverse authors, without ignoring some aspects like the number of stations, time of each one, and interdependence among them (18), is ratified as an adequate evaluation tool. However, according to Wessel et al (19), who evaluated the skills required to manage people with chronic musculoskeletal conditions, it has poor internal consistency (0.48), since the number of stations can be a limitation.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…The OSCE, as a valid and reliable instrument according to the results from this study and as stated by diverse authors, without ignoring some aspects like the number of stations, time of each one, and interdependence among them (18), is ratified as an adequate evaluation tool. However, according to Wessel et al (19), who evaluated the skills required to manage people with chronic musculoskeletal conditions, it has poor internal consistency (0.48), since the number of stations can be a limitation.…”
Section: Discussionmentioning
confidence: 87%
“…Nevertheless, the OSCE is widely used in health education, as reported by Trejo et al, who employed the OSCE to assess clinical skills in physicians (20), or Bujack et al (21), who established the content validity by carefully training simulated patients and showed that normalized evaluation criteria and cross-marking procedures improve inter-marker reliability, with the use of simulated patients being common in simulated practice as a pedagogic strategy accompanied by the use of the OSCE for evaluative follow-up. This practice responds to the educational trends in health by using clinical simulation, a pedagogic strategy in physiotherapy that facilitates skill development and grants security in clinical performance (18,22). To complement Bujack et al, Ward and Willis (23) highlight the importance of preparation in the success of the OSCE validation, criteria considered in our study, in which an OSCE was conducted as a pilot test carried out with fourth-semester physiotherapy students which were then peer-reviewed.…”
Section: Discussionmentioning
confidence: 99%
“…Si bien hay variaciones en la confiabilidad interobservador, por lo general esta es alta y cercana al 1.0. La confiabilidad intercasos puede resultar baja si la evaluación es corta, pero en una duración de 4 horas se reporta una confiabilidad de 0.8 2,4,10 .…”
Section: Examen Clínico Objetivo Estructuradounclassified
“…A lo largo del tiempo se han desarrollado múltiples formas de evaluar el aprendizaje en los estudiantes de medicina, como los exámenes escritos en cualquiera de sus formatos (respuesta de ensayo, respuesta corta u opción múltiple), que son ampliamente usados por su practicidad; aunque su capacidad de evaluación se detiene en los primeros dos niveles de la pirámide de Miller. Los exámenes orales escalan hasta el tercer nivel de la pirámide, en especial los conocidos como «caso largo», pero presentan inconvenientes como una amplia diferencia interevaluador debido a diferencias a la hora de calificar por parte de los docentes 2 . Sin embargo, estos modelos de evaluación apenas han sufrido modificaciones a lo largo del tiempo, al contrario que los modelos de aprendizaje y enseñanza, que distan de una formación meramente basada en adquirir y memorizar conocimientos (saber) y se han centrado en la obtención y formación de distintas habilidades, actitudes y valores complementarias al saber, de lo cual deriva una necesidad de establecer métodos de evaluación que puedan valorar estos 3 .…”
Section: Introductionunclassified
“…La estructura interna de la Guía sintética del evaluador en su totalidad tuvo un Alpha de Cronbach de 0.94, el cual es aceptable según Vogt 19 , y supera el rango de otros estudios equivalentes, los cuales han determinado aspectos psicométricos del ECOE como el Alpha de Cronbach en rangos entre 0.62 y 0.93 [20][21][22][23][24][25] . Para calcular el coeficiente G, se empleó un modelo cruzado anidado considerando como facetas las estaciones y la sede.…”
Section: Contenidounclassified